2020
DOI: 10.3389/fneur.2020.532110
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Intrinsic Brain Activity and Neuroimaging-Based fMRI Classification in Patients With Herpes Zoster and Postherpetic Neuralgia

Abstract: Objective: Neuroimaging studies on neuropathic pain have discovered abnormalities in brain structure and function. However, the brain pattern changes from herpes zoster (HZ) to postherpetic neuralgia (PHN) remain unclear. The present study aimed to compare the brain activity between HZ and PHN patients and explore the potential neural mechanisms underlying cognitive impairment in neuropathic pain patients. Methods: Resting-state functional magnetic resonance imaging (MRI) was carried out among 28 right-handed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Furthermore, we fitted logistic regression, RF, SVM, and NB machine learning models to identify MRP by inputting basic clinical characteristics. We found that the SVM model had the highest accuracy to discriminate MRP from MSP, with a prediction accuracy comparable to previous imaging or EEG-based approaches [ 13 , 18 ].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, we fitted logistic regression, RF, SVM, and NB machine learning models to identify MRP by inputting basic clinical characteristics. We found that the SVM model had the highest accuracy to discriminate MRP from MSP, with a prediction accuracy comparable to previous imaging or EEG-based approaches [ 13 , 18 ].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, restoring arginine bioavailability through exogenous arginine supplementation might be a beneficial approach for treating PHN (Bakshi and Morris, 2016). Notably, a recent study proposed a novel classification method for patients with HZ and PHN based on functional magnetic resonance imaging (fMRI), which indicated that decreased brain activity via the SVM algorithm could be used to classify individuals with different pain conditions (Huang et al, 2020). Notably, ML models also provide a novel identification 10.3389/fnmol.2022.1009677 method for patients with herpetic neuralgia who are at risk of inadequate pain management.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, SVM techniques combined with neuroimaging metrics have been applied to differentiate pain patients from HCs and to predict the outcome of certain interventions ( Bagarinao et al, 2014 ; Zeng et al, 2019 ; Huang et al, 2020 ; Tu et al, 2020b ; Gui et al, 2021 ; Wei et al, 2022 ). The patients with neuropathic pain and the HC were classified by the mean ALFF values of the frontal gyrus and the precuneus using the linear SVM classifier, and the classification accuracy was 86.36% between the PHN patients and HC ( Huang et al, 2020 ). A study identified a neural marker with abnormal FC within the SMN and FPN that could discriminate MwoA patients from HC with a 91.4% accuracy rate ( Tu et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Given these neuroimaging findings on chronic pain, we speculated that patients with CS may also have abnormal changes in structural properties or between-regions FC. In addition, previous studies have applied machine learning techniques to distinguish patients with post-herpetic neuralgia (PHN) and HC using the amplitude of low-frequency fluctuation (ALFF) values ( Huang et al, 2020 ). However, few studies have classified neuropathic pain patients from HC by multimodal neuroimaging features.…”
Section: Introductionmentioning
confidence: 99%